Bacterial Toxin‐Responsive Biomimetic Nanobubbles for Precision Photodynamic Therapy against Bacterial Infections. Issue 18 (19th July 2022) - Zhuge, Deli; Li, Li; Wang, Haonan; Yang, Xuewei; Tian, Dongyan; Yin, Qingqing; Chen, Hao; Weng, Cuiye; Wen, Bin; Lin, Yijing; Huh, Joo Young; Zhang, Xufei; et al.
Abstract: With few options available for the effective treatment of multidrug‐resistant bacteria, photodynamic therapy (PDT) has emerged as a promising therapeutic strategy that does not promote the development of antibiotic resistance. Unfortunately, the beneficial bactericidal effect of PDT is oftentimes accompanied by the uncontrollable production of reactive oxygen species. To overcome this issue, a pore‐forming toxin (PFT)‐responsive biomimetic nanobubble is designed, which is constructed by co‐encapsulating a perfluorocarbon nanoemulsion and a photosensitizer within the red blood cell membrane. It is shown that PFTs derived from three pathogens, including methicillin‐resistant Staphylococcus aureus (MRSA), group A Streptococcus (GAS), and Listeria monocytogenes (LM), can be effectively absorbed by the nanobubble. Upon toxin absorption, the formation of pores on the nanobubble surface allows the accelerated release of oxygen dissolved inside the nanoemulsion along with the photosensitizer, thus resulting in enhanced PDT and bactericidal efficacy. In three skin infection models, treatment with the nanobubbles results in significantly decreased lesion formation and reduced inflammation. In addition to oxygen, the platform can be used to deliver nitric oxide in a bacterial toxin‐dependent manner. Overall, biomimetic nanobubbles may work as a broad gas delivery system that is capable of responding to a variety of PFT‐based stimuli for precision PDT. Abstract : Secreted bacterial toxins such as pore‐forming toxins are capable of governing the photodynamic therapy effect of RBC(IR780)‐PFC(O2 ) nanobubble under near infrared irradiation for treatment of source bacterial infections. Leveraging this unique approach, what would normally be considered a negative aspect of bacterial infections (i.e., toxin secretion) is able to be transformed into a positive.